Classification of pH levels using a mobile phone - Tang, Tung Lieng. (2012)
“To get rich never risk your health. For it is the truth that health is the wealth of wealth.” [1] This is a quote by Richard Baker, a British broadcaster. The trend of health conscious is getting more popular as people know that health cannot be judged by their wealth. Hence, people usually now schedule annual medical check-up. Even now, Singapore Government is advertising through media to do regular check-up more often, especially for senior citizens, to prevent any sudden terminal illness. Other than regular medical check-up, pH testing on saliva and urine comes into the picture for doing a simple check-up. However, people with poor eyesight and color blindness, might determine the wrong pH level. Therefore, since mobile phone is known to be the most convenient and portable device, this project aims to create a mobile application that solves the problem of determining the wrong pH level. This mobile application is implemented as a Java application to be operated on a Symbian Operating System-based mobile phone. With the help of well-written image processing and clustering techniques, this application is definitely achievable. Experiments and sufficient testing are done to ensure the robustness of the application and efficiency of the algorithm used.